(untitled) (Annual of the Faculty of Philosophy in Skopje, 2020)
For the remarkable lectures permeated with numerous funny details and lucid inventions, For the picturesque debates on different subjects and in various occasions, For the archeological stories nuanced with unbelievably charming sparkles of illumination and humorous approach, For the long terrain walks through the site of Stobi and the discussions about the stratigraphic amplitude of the Episcopal basilica, For the professional training for survival in the wasteland surrounded by the elusive shadow of hauling wolves For the walk towards the archaeological site of Scupi and the brilliant exposition of what might or cannot be seen there, For the friendly suggestions on the professional orientation that defines the aura of each individual with a recognizable social identity, For ever and always accessible courtesy for archaeological and/or historical discourse For the fascinating comments of the actual socio-political reality which, by default, is always an echo of unresolved dilemmas or pending issues from yesterdays or the distant past, For the advises on how to help the mediocre people not to become subversive antibodies in the sensitive and, often, weak tissue of Macedonian archaeology,